2020
DOI: 10.22146/ijp.1120
|View full text |Cite
|
Sign up to set email alerts
|

Eleutherine palmifolia (L.) Merr. Extract Increases The Crypts and Caspase-3 Expression in Colitis-Associated Colon Cancer Model

Abstract: It is known that Eleutherine palmifolia (L.) Merr contains flavonoid and polyphenol as bioactive compounds that have the ability as chemopreventive agents. This study aims to examine the effect of Eleutherine palmifolia (L.) Merr extract (EPE) on colon histopathology and the enhancement of caspase-3 expression in BALB/c mice of colitis-associated colon cancer (CAC) model. Thirty Balb/c female mice were used in this study and were divided into six groups. Five mice in one group were normal or negative control (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Based on research, it shows that the ethanol extract of S. palmifolium can inhibit the growth of HeLa cervical cancer cells (Muti'ah et al, 2018). Another study showed that the administration of ethanol extract of S. palmifolium could trigger the apoptotic activity of cancer cells both intrinsically and extrinsically (Muti'ah et al, 2020). This is supported by previous studies, which showed that S. palmifolium could function as colonic anti-cancer agents (Li et al, 2008).…”
Section: Introductionmentioning
confidence: 53%
“…Based on research, it shows that the ethanol extract of S. palmifolium can inhibit the growth of HeLa cervical cancer cells (Muti'ah et al, 2018). Another study showed that the administration of ethanol extract of S. palmifolium could trigger the apoptotic activity of cancer cells both intrinsically and extrinsically (Muti'ah et al, 2020). This is supported by previous studies, which showed that S. palmifolium could function as colonic anti-cancer agents (Li et al, 2008).…”
Section: Introductionmentioning
confidence: 53%
“…One of the most common methods to analyze various tissue healing or pathology at the microscopic structural level is hematoxylin eosin staining (Nurrahma et al, 2022;Mutiah et al, 2020, Wardani et al, 2022Pananchery & Gadgoli, 2021). Histopathological staining using hematoxylin-eosin (HE) is one of the most common analytical methods.…”
Section: Histology Based Microscopically Scoringmentioning
confidence: 99%